PERAN KOMITE SEKOLAH DALAM MENYOKONG PENINGKATAN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH AL-KAUTSAR MEDAN - Ridwan, Ahmad; Azis, Abdul; Jannah, Fathul (Fakultas Agama Islam Universitas Al Washliyah, 2024)
This study aims to examine the role of the School Committee in supporting the improvement of education quality at Madrasah Ibtidaiyah Al-Kautsar Medan. In the context of Indonesian education, the role of the School Committee as an important partner in school management is increasingly recognized for its significance. This study uses a qualitative approach with data collection techniques through interviews and observations. The results of the study indicate that the School Committee plays a strategic role in curriculum development, facility management, and human resource empowerment at Madrasah Ibtidaiyah Al-Kautsar Medan. However, there are still several challenges in the implementation of the School Committee's role, such as the lack of active involvement from School Committee members and resource limitations. Therefore, this study also identifies several recommendations to strengthen the role of the School Committee in supporting the improvement of education quality at Madrasah Ibtidaiyah Al-Kautsar Medan, including increasing the involvement of School Committee members, improving coordination between the School Committee and the school, and providing training and support to School Committee members. It is hoped that the results of this study can contribute positively to the development of strategies and policies to enhance the quality of education at Madrasah Ibtidaiyah Al-Kautsar Medan and other educational institutions.